NUKSMA DAN MUNGGUH DALAM PERTUNJUKAN WAYANG PURWA GAYA SURAKARTA - Sunardi Sunardi (Gelar : Jurnal Seni Budaya, 2010)
Nuksma and mungguh are the aesthetic orientation of wayang purwa performance of Surakarta style. Nuksma (expressive) gives an understanding that the shadow play the puppeteer performs  has the impression of life. Mungguh (logic) shows that the wayang performance that the puppeteer expresses has a conformity with the rules of puppetry. The concepts ofmungguh andnuksma are  formed by three elements, that is, (a) medium; expression, and (c) a pattern of suitability. Medium is the raw material processed into a variety ofgarap material. Expression is understood as the  puppeteer's strength in performing antawecana (dialogues), sabetan, and vocal-instrumental. The pattern of suitability refers to the creation of synergistic relationship between matter, expression,  and the rules of puppetry. The implementation of nuksma and mungguh concepts at the Samodera Mingkalbu scene, the story of Bima Sekti perfomed by Nartasabda can be known through the  expression of catur (talk), sabet and karawitan for wayang performance, the response of the audience and social context of Javanese culture.Key words: nuksma and mungguh, matter, expression, pattern of suitability, puppeteer, wayang performance.